1991
DOI: 10.2134/agronj1991.00021962008300050002x
|View full text |Cite
|
Sign up to set email alerts
|

Witchweed Management by Sorghum‐Sudangrass Seed Size and Stage of Harvest

Abstract: Careful cultural management of field crops has become imperative in countries where chemical measures are not economically feasible. The occurrence of the endemic parasitic witchweed [Striga hermonthica (Del.) Benth] in production fields of sorghum‐sundangrass hybrid [Sorghum bicolor (L.) Moench ✕ S. sudanense Stapf. cv. Piper], Pioneer brand hybrid 988 (coded P988), is one example that requires such procedures. Study objectives were to relate: (i) P988 seed size (large and small) to witchweed germination, P98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Striga infests >40 % of arable land in SSA (Lagoke et al 1991) and causes yield losses of up to 100 %. Striga is so ingeniously adapted to its environment and host plants (Bebawi and Metwali 1991) that it will germinate only in response to specific chemical cues present in host root ex-udates or certain non-host plants (Parker and Riches 1993;Yoder 1999). Seeds can remain dormant but viable in the soil for >10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Striga infests >40 % of arable land in SSA (Lagoke et al 1991) and causes yield losses of up to 100 %. Striga is so ingeniously adapted to its environment and host plants (Bebawi and Metwali 1991) that it will germinate only in response to specific chemical cues present in host root ex-udates or certain non-host plants (Parker and Riches 1993;Yoder 1999). Seeds can remain dormant but viable in the soil for >10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Striga weakens the host, wounding its outer root tissues and absorbing its supply of moisture, photosynthates, and minerals (Tenebe and Kamara, 2002), and is so ingeniously adapted to its environment (Bebawi and Metwali, 1991) and integrated with the host that it will only germinate in response to specific chemical cues present in root exudates of its hosts or certain nonhost plants (Yoder, 1999; Parker and Riches, 1993). It also causes “phytotoxic” effects within days of attachment to its hosts (Frost et al, 1997; Gurney et al, 1999), whose underlying mechanism has not yet been elucidated (Gurney et al, 2006).…”
mentioning
confidence: 99%
“…For example, sorghum-sudangrass (Sorghum bicolor [L.] Moench × Sorghum sudanese [Piper] Stapf) has been reported to control johnsongrass (Sorghum halepense [L.] Pers.) (Forney et al 1985) and witchweed (Striga hermonthica [Del] Benth) (Bebawi and Mutwali 1991). Siemens (1963), in a summary of a long-term crop rotation study at Indian Head, SK, indicated that a 1-yr green manure crop in a 3-yr rotation reduced wild oat dockage in spring wheat grain crops relative to continuous wheat or wheat-fallow systems.…”
mentioning
confidence: 99%